Santé mentale et maladies mentales des jeunes francophones de 15 à 24 ans : données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale 2012 - Bouchard, Louise; Batista, Ricardo; Colman, Ian (Minorités linguistiques et société, 2018)
a plupart des maladies mentales apparaissent à l’adolescence ou au début de la vie adulte ; elles influent sur les réussites scolaires, les possibilités et les succès professionnels ainsi que les relations personnelles et peuvent avoir des répercussions tout au long de la vie. Bien que la majorité des jeunes traversent leur adolescence sans problèmes, une proportion suffisamment importante montre toutefois un profil préoccupant dont il faut prendre acte. L’objectif de cet article est de brosser, à partir des données de l’Enquête sur la santé dans les collectivités canadiennes – Santé mentale (ESCC-SM 2012), un portrait de la santé mentale des jeunes francophones de 15 à 24 ans vivant en situation linguistique minoritaire et de le comparer à celui des jeunes francophones vivant au Québec. Mots-clés : identité ethnolinguistique, continuité culturelle, minorité francophone, jeunes adultes, santé mentale

Health profile of English-speaking minority communities in Quebec [infographic] - Bouchard, Louise; Sampasa-Kanyinga, Hugues; Mukaneza, Anne (2018)

Profil santé des communautés anglophones en situation minoritaire au Québec [infographie] - Bouchard, Louise; Sampasa-Kanyinga, hugues; Mukaneza, anne (2018)

Linguistic mortality gradients in Quebec and the role of migrant composition - Lo, Ernest; Tu, Mai Thanh; Trempe, Normand; Auger, Nathalie (Canadian Journal of Public Health, 2018)
Objective Anglophones and Allophones in Quebec (Canada) have lower mortality than Francophones, despite being linguistic minorities. This study assesses whether (1) language is a risk factor for mortality after accounting for migrant composition and (2) interprovincial migrants differ in mortality with respect to Quebec-born individuals. Methods We analyzed death records between 2004 and 2008 from Quebec (all-cause and main causes) and population data from the 2006 census to estimate age-adjusted mortality rates according to language and migrant status. Risk ratios by language and migrant status, adjusted for age, sex, and socioeconomic status, were estimated using Poisson generalized estimating equations. Results Francophone Quebec-borns had the highest mortality. Among Quebec-borns, Anglophones [RR= 0.85, 95% CI (0.79–0.91)] and Allophones [RR = 0.16, 95 %CI (0.12–0.22)] had lower mortality relative to Francophones. Interprovincial migrants had lower mortality (Anglophones [RR = 0.58, 95% CI (0.53–0.63)], Francophones [RR = 0.55, 95% CI (0.50–0.60)]) relative to Francophone Quebec-borns (Allophones were excluded due to small sample size). Among immigrants, mortality was lower for Francophones [RR = 0.62, 95% CI (0.57–0.67] and Allophones [RR = 0.35, 95% CI (0.31–0.38], but not Anglophones [RR = 0.92, 95% CI (0.84–1.01)], relative to Francophone Quebec-borns. Conclusion In Quebec, linguistic disparities in mortality remained after accounting for migrant status, and both Francophone and Anglophone interprovincial migrants in Quebec had lower mortality than Quebec-born Francophones. Public health initiatives to reduce linguistic disparities in health should account for migrant status.

Demographic Profile of the English-Speaking Communities - Pocock, Joanne (2018)

Socio-demographic profile of the population aged 65 and over. Province of Québec. Based on the 2016 census of Canada - Pocock, Joanne (Community Health and Social Services Network, 2018)

Améliorer la santé et le bien être des Madelinots anglophones. Une stratégie pour un développement sain des jeunes - Richardson, Mary; Ledoux, Jaldhara Jacinthe (Council for Anglophone Magdalen Islanders, 2018)

Portrait de la prématurité et des naissances ayant un faible poids pour l’âge gestationnel dans les communautés linguistiques au Québec, 1989 à 2010 - Tu, Mai Thanh; Bilodeau-Bertrand, M.; Auger, Marianne (Institut national de santé publique du Québec, 2018)

Portrait of preterm and small-for-gestational-age births by linguistic community in Québec, 1989 to 2010 - Tu, Mai Thanh; Bilodeau-Bertrand, Marianne; Auger, Nathalie (Institut national de santé publique du Québec, 2018)

Health profile of linguistic communities in Québec - Tu, Mai. Thanh; Lussier, Marie-Hélène.; Martel, Sylvie; Blaser, Christine (Institut national de santé publique du Québec, 2018)

Portrait de santé des communautés linguistiques du Québec - Tu, Mai Thanh; Lussier, Marie-Hélène; Martel, Sylvie; Blaser, Christine (Institut national de santé publique du Québec, 2018)